Effect of glycerol on the viability and fertility of cooled bovine semen - Papa, Patricia M. [UNESP]; Maziero, Rosiara D. [UNESP]; Guasti, Priscilla N. [UNESP]; Junqueira, Cassio R.; Freitas-Dell'Aqua, Camila P. [UNESP]; Papa, Frederico Ozanam [UNESP]; Vianna, Felipe P. [UNESP]; Alvarenga, Marco Antonio [UNESP]; Crespilho, Andre M.; Dell'aqua Junior, José Antônio [UNESP] (Elsevier B.V., 2015)
The aim of the present study was to compare the viability and fertility of bovine semen diluted in Botu-Bov (BB) commercial extender with and without the cryoprotectant glycerol then cooled at 5 C for 24 hours in the Botu-Flex passive cooling system and of semen diluted in BB with glycerol then frozen. One ejaculate of 30 Nelore Bos taurus indicus bulls between 24 and 30 months of age was used for in vitro analysis. Sperm kinetics and cell viability were analyzed using computer-assisted sperm analysis and flow cytometry, respectively. Three Nelore bulls approximately 30 month old were used for in vivo test using fixed-time artificial insemination for the fertility analysis. The ejaculates were divided into three experimental groups: semen in BB extender with 7% glycerol cooled at 5 degrees C for 24 hours (cooled semen with cryoprotectant), semen in BB without glycerol cooled at 5 degrees C for 24 hours (cooled semen without cryoprotectant), and semen diluted in BB with 7% glycerol then subsequently frozen rather than cooled (frozen semen). For the fertility analysis, 762 Nelore cows (B taurus indicus) were randomly inseminated using fixed-time artificial insemination. For the groups corresponding to cooled semen with cryoprotectant, cooled semen without cryoprotectant, and frozen semen, 278, 268, and 216 cows were inseminated, respectively, and the resulting conception rates were 51% a, 44%ab and 41%b (P < 0.05), respectively. In conclusion, the fertility rates improved, when samples were cooled with glycerol at 5 degrees C for 24 hours compared with the frozen samples. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Bovine; Semen; Cooling; Fixed-time artificial insemination